2009
DOI: 10.1074/jbc.m805990200
|View full text |Cite
|
Sign up to set email alerts
|

Synphilin-1A Inhibits Seven in Absentia Homolog (SIAH) and Modulates α-Synuclein Monoubiquitylation and Inclusion Formation

Abstract: Parkinson disease (PD) is characterized by the presence of ubiquitylated inclusions and the death of dopaminergic neurons. Seven in absentia homolog (SIAH) is a ubiquitin-ligase that ubiquitylates ␣-synuclein and synphilin-1 and is present in Lewy bodies of PD patients. Understanding the mechanisms that regulate the ubiquitylation of PD-related proteins might shed light on the events involved in the formation of Lewy bodies and death of neurons. We show in this study that the recently described synphilin-1 iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 50 publications
(70 reference statements)
0
30
0
Order By: Relevance
“…SIAH is present in Lewy bodies (9) and monoubiquitinates α-synuclein at the same lysine residues that are monoubiquitinated in α-synuclein immunopurified from Lewy bodies (5,10). Most importantly, we found that in the presence of proteolytic inhibitors, monoubiquitination of α-synuclein promoted by SIAH leads to a marked increase in the aggregation of α-synuclein and formation of inclusions, which are toxic to cells (10)(11)(12). Therefore, our data indicate that monoubiquitination by SIAH might play a primary role in the aggregation and toxicity of α-synuclein and possibly in the formation of Lewy bodies.…”
mentioning
confidence: 67%
“…SIAH is present in Lewy bodies (9) and monoubiquitinates α-synuclein at the same lysine residues that are monoubiquitinated in α-synuclein immunopurified from Lewy bodies (5,10). Most importantly, we found that in the presence of proteolytic inhibitors, monoubiquitination of α-synuclein promoted by SIAH leads to a marked increase in the aggregation of α-synuclein and formation of inclusions, which are toxic to cells (10)(11)(12). Therefore, our data indicate that monoubiquitination by SIAH might play a primary role in the aggregation and toxicity of α-synuclein and possibly in the formation of Lewy bodies.…”
mentioning
confidence: 67%
“…Mouse anti-histone3 (1:1000) was obtained from Abcam. Rabbit anti-seven in absentia homologue (Siah) (1:500) was a gift from Dr. Simone Engelender (Technion-Israel Institute of Technology) and has been described in earlier studies (38,39). Rabbit affinity-purified anti-SR antibody (0.2-0.3 g/ml) (18) or guinea pig anti-SR have also been described elsewhere (40).…”
mentioning
confidence: 99%
“…While Siah-1, and much more efficiently Siah-2, has been reported to interact with alphasynuclein resulting in its monoubiquitylation [50], under our assays conditions we were not able to detect any alphasynuclein modification following Siah-1 expression. The apparent conflicting results can be explained by the fact that monoubiquitylation of alpha-synuclein is quantitatively a minor modification [50,63] that could not be readily detected by direct immunoblotting of whole cell extracts, and in any case Siah-1 expression did not significantly affect alpha-synuclein degradation by the proteasome pathway in the absence of synphilin-1 (Fig. 8).…”
Section: Discussionmentioning
confidence: 99%